2021
DOI: 10.1038/s41598-020-80927-5
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind randomized clinical trial of high frequency rTMS over the DLPFC on nicotine dependence, anxiety and depression

Abstract: High frequency repetitive transcranial magnetic stimulation (HF-rTMS) over the left dorsolateral prefrontal cortex (L-DLPFC) is a widely applied treatment protocol for chronic smoking and major depressive disorder. However, no previous study has measured the effects of rTMS on both nicotine consumption and anxiety/depression in the same volunteers despite the relationship between them. The aim of this work was to evaluate the efficacy of 10 daily sessions of HF-rTMS over the L-DLPFC in chronic cigarette smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
(22 reference statements)
1
18
1
Order By: Relevance
“…Future studies to validate and clarify this sex difference are necessary. Brain-based smoking cessation interventions, such as transcranial magnetic stimulation, have been evaluated for smoking cessation ( Li et al, 2017 ) and reduced cigarette consumption and nicotine dependence after stimulation of the insula ( Dinur-Klein et al, 2014 ) or the left dorsolateral prefrontal cortex ( Li et al, 2020 ; Abdelrahman et al, 2021 ). Such interventions may improve their efficacy by targeting different brain regions, and perhaps different subregions of the insula, in men vs women.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies to validate and clarify this sex difference are necessary. Brain-based smoking cessation interventions, such as transcranial magnetic stimulation, have been evaluated for smoking cessation ( Li et al, 2017 ) and reduced cigarette consumption and nicotine dependence after stimulation of the insula ( Dinur-Klein et al, 2014 ) or the left dorsolateral prefrontal cortex ( Li et al, 2020 ; Abdelrahman et al, 2021 ). Such interventions may improve their efficacy by targeting different brain regions, and perhaps different subregions of the insula, in men vs women.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the literature associates internet addiction with tobacco smoking, heavy drinking, substance abuse, and sexual promiscuity in both genders, although at varying degrees (26)(27)(28)(29). Negative emotions seem to be a core common effector in dysfunctional eating, internet addiction, and smoking (5,17,26,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics underlying the relationship between smoking and dysfunctional eating may be more complex than they seem to be. Imaging studies report abnormal activity of brain regions associated with self-referencing and emotional processing (e.g., medial prefrontal cortex and other brain regions) among smokers, AN and BN patients, and obese individuals who eat in response to aversive states (5,30,31,38,39). Psychopathological features closely linked to dysfunctional emotional processing are documented core correlates of internet addiction, smoking, binge drinking, substance abuse, problematic gambling, and maladaptive patterns of physical activity (26).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers have conducted therapeutic explorations using rTMS for psychoneurological disorders and SUD. Previous studies have made continuous attempts for treatment modalities, from low frequency ( 28 , 29 ) to high frequency ( 18 , 30 ), and from rTMS to TBS or from the original stimulation site (e.g., L-DLPFC) to other sites (e.g., mPFC) ( 11 ). Current research suggested that the stimulation of the DLFPC region (area within the executive control network) by modalities such as high-frequency rTMS or iTBS effectively reduced craving, which might be associated with enhanced executive function ( 12 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Executive function, as an important part of cognitive function, has gained increasing attention in studies on SUD, which has found that long-term drug abuse would cause widespread impairment of executive function ( 16 , 17 ). Lower executive function has been reported to be associated with relapse ( 18 ), and improving executive function reduces relapse and improves treatment outcomes for SUD ( 19 ). Executive function may therefore be an effective novel therapeutic target for improving drug addiction and relapse and a valid predictor of treatment efficacy for SUD.…”
Section: Introductionmentioning
confidence: 99%